Tpeak-Tend dispersion as a predictor for malignant arrhythmia events in patients with vasospastic angina - Xianpei, Wang; Sha, Wu; Chuanyu, Gao; Juanjuan, Yan; Chong, Chen; Yongen, Shi; Yu, Feng; Zhenhao, Lin (International journal of cardiology, 2017)
Tpeak-Tend interval (Tp-e interval) in electrocardiogram (ECG) has been reported to predict malignant arrhythmia events (MAE) in ST-segment elevation myocardial infarction and ion channelopathy. Tp-e interval and other ECG parameters as predictors for MAE was evaluated in patients with vasospastic angina (VA). Sixty-two patients with VA (Non-MAE group) and 20 patients with VA complicated by MAE (MAE group) were enrolled in our Division of Cardiology between January 2010 and December 2015. Continuous variables were analyzed by t-test and categorical variables by Chi-square analysis. Patients with MAE showed greater QTc (corrected QT interval) dispersion (P=0.005), Tp-ec (corrected Tp-e) interval (P=0.001), Tp-ec dispersion (P<0.001) and Tp-e/QT ratio (P<0.001) than those in non-MAE groups when ST-segment elevated. After elevated ST-segment returned, there were no significant differences in these ECG parameters between two groups (All P>0.05). At univariate binary logistic regression analysis QTc dispersion (odds ratio(OR)=1.133; P=0.013), Tp-ec (OR=1.058; P=0.003), Tp-e/QT (OR=1.403; P=0.001), and Tp-ec dispersion (OR=1.497; P=0.004) were significantly associated with MAE. At multivariable logistic regression analysis, Tp-ec dispersion remained a predictor of MAE. Receiver operating characteristic (ROC) curve analysis showed that only AUC (Area under curve) of Tp-ec dispersion had significant difference with those in QTc dispersion (P<0.001), Tp-ec (P=0.003), and Tp-e/QT ratio (P=0.012), respectively. QTc dispersion, Tp-ec, Tp-e/QT and Tp-ec dispersion were significantly increased in VA patients with MAE than those without MAE when coronary spasm was onset. Prolonged Tp-ec dispersion was the best discriminators and a strong independent predictor of MAE in VA patients.